GREEN TOURISM MANAGEMENT FOR SUSTAINABLE TOURISM DEVELOPMENT IN THE AGE OF DISRUPTION - Ariyanto Ariyanto (Sean Institute, 2022)
Tourism is one of the most important economic activities in the world . The idea of sustainable tourism is something that many experts talk about lately, because we are now in the Industrial Era 4.0 or often known as the Era of Disruption. And the discussion on the idea of sustainable tourism cannot be separated from the discussion on environmentally conscious tourism. Because there is currently a tendency for people to care more about nature conservation and sustainable tourism, the concept of green tourism will be very attractive to every actor involved in the tourism sector. This is because green tourism takes advantage of the fact that people want to travel without negatively impacting the environment. The purpose of this study is to describe the influence of the idea of green tourism on the sustainable tourism sector. To provide an overview of the topic under study, this study uses qualitative techniques and descriptive methods. According to research findings, green tourism management has a significant impact on sustainable tourism. This is because the concept of green tourism management emphasizes the idea of being friendly with nature and the environment, as well as making a significant contribution to the economy of local communities that have not been affected by economic empowerment..